Le Brésil au cœur des stratégies spatiales du recrutement des clubs européens de football - Bertrand Piraudeau (Confins)
Since the end of the 1990s, the number of Brazilian footballers playing in the international professional clubs increases constantly. The principal European championships (Germany, England, Spain, France, Italy and Portugal) are very courted by the Brazilian players. The history of the relations between territories and spatial strategies of recruitment developed by the European football clubs reveals a productive system of Brazilian players and very organized migratory channels between Europe and Brazil.